The HPT Model Applied to a Boutique‐Style Online Retail Store. Issue 7 (August 2015) - Hayes, Rebecca; Godwin, Caroline; Butts, Danielle; Martin, Florence
<x xml:space="preserve">Abstract</x> Suzy Q's is a retail business located in the southeastern United States. It offers hand‐knitted scarves; handmade hair accessories; handcrafted beaded jewelry such as necklaces, bracelets, and earrings; small handmade children's toys; and stock and custom‐printed T‐shirts. It began operations in early 2014. The owners established an online store and developed plans to sell items at local craft fairs and farmers' markets in the southeastern United States. During its initial launch, the business generated limited orders for its products. In the beginning there was a limited amount of advertising using social media, which consisted of establishing a Facebook page, posting notifications on the business's Facebook page, and posting notifications about the business to the owners' personal contacts on Facebook. Despite establishing a web presence and utilizing social media in its first year of operations, Suzy Q's did not generate a significant number of orders and received very little revenue. The owners of Suzy Q's, our client, established a goal to generate at least $700 per month in revenue for the calendar year 2015. Our analysis of the business revealed that the managers and employees had the skills needed to perform the work, but the lack of orders presented an obstacle to achieving their business goals. After completing a performance analysis, we recommended that Suzy Q's establish a single online presence, implement a marketing effort, establish a local presence, create a dedicated studio space, and create a formal business plan. It was our belief that Suzy Q's had the potential to reach its goals set for 2015 and beyond if these solutions were implemented.